2010
DOI: 10.3892/ijo_00000704
|View full text |Cite
|
Sign up to set email alerts
|

Dietary polyphenol quercetin targets pancreatic cancer stem cells

Abstract: Abstract. According to the cancer stem cell hypothesis the aggressive growth and early metastasis of pancreatic cancer may arise through dysregulation of self-renewal of stem cells in the tissue. Since recent data suggest targeting of cancer stem cells by some dietary agents we studied the effect of quercetin, a major polyphenol and flavonoid commonly detected in many fruits and vegetables. Using in vitro and in vivo models of pancreatic cancer stem cells we found quercetin-mediated reduction of self-renewal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Several studies reported similar biosafety profiles for SF combined with other drugs. 21 , 29 , 30 To our knowledge, we are the first to show that SF enhanced the cytotoxicity of CIS and 5-FU towards HNSCC–CSCs.…”
Section: Discussionmentioning
confidence: 77%
“…Several studies reported similar biosafety profiles for SF combined with other drugs. 21 , 29 , 30 To our knowledge, we are the first to show that SF enhanced the cytotoxicity of CIS and 5-FU towards HNSCC–CSCs.…”
Section: Discussionmentioning
confidence: 77%
“…[143] Pancreatic cancer Self-renewal capability of putative pancreatic cancerous stem cells was inhibited by Qu. [144] Pancreatic cancer Qu, alone and in combination with gemcitabine, robustly induced cell death, leading to a decrease in cell growth in pancreatic cancer cells. [145] Pancreatic cancer…”
Section: Endometrial Cancermentioning
confidence: 99%
“…By inducing apoptosis, autophagy, and cell cycle arrest, blocking cell migration, and inhibiting fatty acid synthesis required for de novo membrane synthesis, Qu elicits antitumor effects [201][202][203][204][205]. More recently, Qu has been shown to inhibit self-renewal capacity of putative pancreatic cancer stem cells [144]. Several in vivo animal models indicate suppressed local and distant tumor growth post administration of Qu in pancreatic cancer cases.…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…The flavonol quercetin is a molecule of medical interest, as it possesses anticancer potential [86]. In fact, quercetin targets several types of CSCs, including pancreatic [87], breast [88], and gastric [89] stem cells.…”
Section: Flavonoids Targeting Cancer Stem Cellsmentioning
confidence: 99%